Optimizing Swathing and Chemical Desiccant Timing to Accelerate Winter Carinata Maturation. (1st July 2018) - Seepaul, Ramdeo; Marois, Jim; Small, Ian; George, Sheeja; Wright, David L.
Abstract : Core Ideas: Brassica carinata is an emerging dedicated oilseed feedstock for 'drop‐in' biofuels. Sequential flowering produces a mixture pods of different maturity. Harvest aids enhance seed maturation, crop dry down with little effect on yield. Applying harvest aid 14 to 21 d after physiological maturity when seed moisture is <28.5% accelerate transition to summer crops by 7 to 14 d. Brassica carinata (carinata) is an emerging dedicated oilseed feedstock for 'drop‐in' biofuels and renewable bioproducts. There is great potential for carinata to be produced as a winter crop providing economic and environmental benefits in the Southeast United States. The indeterminate flowering of carinata produces pods of different maturity making it difficult to determine the optimum harvest time. The objective of this study was to determine the effects of harvest aid and application timing on crop maturation, seed and oil yields, and fatty acid composition. B. carinata was evaluated in a 2‐yr field study at NFREC, Quincy, FL, during the 2014–2015 and 2015–2016 growing seasons. Treatments were initiated when seed moisture was at 501 to 558 g kg –1 and continued at 7 d intervals for 4 wk. In 2015, harvesting at 21 d after physiological maturity (DAPM) produced 28% greater yield than earlier harvest dates while in 2016, harvesting at 14 DAPM or later produced 31% greater yields than earlier harvests. Swathing reduced seed yield by 11% relative to control in 2015, however, no differences occurred in 2016. Seed shattering increased with maturation regardless of harvest aid and was greatest at 21 DAPM. The use of a harvest aid 14 to 21 DAPM, when seed moisture is <285 g kg –1 and more than 80% of the seeds have changed color, would accelerate the transition to summer crops by 7 to 14 d. These results indicate the potential of harvest aids to accelerate seed dry‐down and uniformity thereby facilitating the timely planting of subsequent summer crops.